A New Centrosaurine Ceratopsid, Machairoceratops cronusi gen et sp. nov., from the Upper Sand Member of the Wahweap Formation (Middle Campanian), Southern Utah - Lund, E.K.; O'Connor, P.M.; Loewen, M.A.; Jinnah, Z.A. (Public Library of Science, 2016)
The Upper Cretaceous (middle-late Campanian) Wahweap Formation of southern Utah contains the oldest diagnostic evidence of ceratopsids (to date, all centrosaurines) in North America, with a number of specimens recovered from throughout a unit that spans between 81 and 77 Ma. Only a single specimen has been formally named, Diabloceratops eatoni, from the lower middle member of the formation. Machairoceratops cronusi gen. et sp. nov., a new centrosaurine ceratopsid from the upper member of the Wahweap Formation, is here described based on cranial material representing a single individual recovered from a calcareous mudstone. The specimen consists of two curved and elongate orbital horncores, a left jugal, a nearly complete, slightly deformed braincase, the left squamosal, and a mostly complete parietal ornamented by posteriorly projected, anterodorsally curved, elongate spikes on either side of a midline embayment. The fan-shaped, stepped-squamosal is diagnostic of Centrosaurinae, however, this element differs from the rectangular squamosal in Diabloceratops. Machairoceratops also differs in the possession of two anterodorsally (rather than laterally) curved epiparietal ornamentations on either side of a midline embayment that are distinguished by a posteromedially-oriented sulcus along the entire length of the epiparietal. Additionally, the parietosquamosal frill is lacking any other epiossifications along its periphery. Machairoceratops shares a triangular (rather than round) frill and spikelike epiparietal loci (p1) ornamentation with the stratigraphically lower Diabloceratops. Both parsimony and Bayesian phylogenetic analyses place Machairoceratops as an earlybranching centrosaurine. However, the parsimony-based analysis provides little resolution for the position of the new taxon, placing it in an unresolved polytomy with Diabloceratops. The resultant Bayesian topology yielded better resolution, aligning Machairoceratops as the definitive sister taxon to a clade formed by Diabloceratops and Albertaceratops. Considered together, both phylogenetic methods unequivocally place Machairoceratops as an early-branching centrosaurine, and given the biostratigraphic position of Machairoceratops, these details increase the known ceratopsid diversity from both the Wahweap Formation and the southern portion of Laramidia. Finally, the unique morphology of the parietal ornamentation highlights the evolutionary disparity of frill ornamentation near the base of Centrosaurinae.
Keywords: Campanian; cladistics; morphology; orbit; sister group; spike; Utah